Methods of drying technology and types of drying kilns gystification - Ozarkiv, Igor; Kobrinovch, Myhaylo; Ozarkiv , Valentyna (Forestry, Forest, Paper and Woodworking Industry, 2024)
Conditions of drying in Ukraine have been analysed. The ways of the further drying engeneering development have been shown.